PRODUCTION NETWORKS AND ACTORS OF THE RECYCLING NETWORK OF THE URBAN ECONOMY OF RIO DE JANEIRO - da Cruz, Uilmer Rodrigues Xavier; Garcia, Ricardo Alexandrino (Seven Editora, 2025)
This article seeks to understand how the recycling production network, which enables the flow of recyclable materials between cooperatives and the recycling industry, takes place. While, articulated in a network, it is interesting to understand how the relationships of the main actors are built - companies, the State, social groups, cooperatives and waste pickers - and how formal and informal, material and immaterial, sometimes cooperative, sometimes conflictive modes of exchange are built. The spatial cut of the research comprises the actors of the Metropolitan Region of the state of Rio de Janeiro and for the analyses made in the article, the concept of productive spatial circuit was adopted as a theoretical perspective. In this sense, Corrêa (1997) elucidates us with what would be a geographical network, Henderson et. al. (2011) contributes to the analysis of the capitalist production system with the concept of production network, while dialoguing with Santos (2011), Milanez & Santos (2013) and Dicken (2015). Itpresents, from direct observation and the documents analyzed[1], the actors that make up the recycling of the state of Rio de Janeiro and how they are articulated in social and productive networks composed of different actors. In view of this, it is thus assumed that the phenomenon of waste picking represents the practice of social subjects, whose trajectories are marked, specifically, by the exclusionary and exploitative functioning of labor in the capitalist system of production and that recycling networks are part of a system composed of various social actors, playing important roles. However, at the same time, recyclable material collectors make up the weakest link in the recycling production network, or the 'garbage game'. [1] Theses, dissertations, books and scientific articles were analyzed, which could contribute significantly to the reflection presented here. DOI: https://doi.org/10.56238/sevened2025.011-012